NGAWI RESORT POLICE EFFORTS IN OVERCOMING WILD RACING CRIME THAT DISTURBING TRAFFIC IN NGAWI DISTRICT - Septian Bayu Triatmojo; Herwin Sulistyowati; Supriyono (PT Akselerasi Karya Mandiri, 2023)
This study raises two issues, namely the legal aspects of illegal racing within the jurisdiction of the Ngawi resort police according to Law Number 22 of 2009 concerning Road Traffic and Transportation and to find out the efforts of the Ngawi resort police in controlling illegal racing in Ngawi district. The legal aspects of illegal racing within the jurisdiction of the Ngawi resort police according to Law Number 22 of 2009 concerning Road Traffic and Transportation are regulated in several articles including Article 21 concerning vehicle speed, Article 115 concerning the prohibition of speeding, Article 229 concerning traffic accidents, Article 235 and Article 310 concerning traffic crimes. The existence of Law Number 22 of 2009 concerning road transport traffic has a crucial and strategic role in supporting the joint commitment to tackling illegal racing among the community because there have been several cases of illegal racing in Ngawi regency. Controlling wild racing in the district Ngawi was attempted by the police Ngawi in humanist ways. The first is Friday chat. Polres Ngawi in a proactive manner carry out Friday Chat which is provided container Polres Ngawi for listening and accommodating various societal complaints, mainly in a matter of wild racing information. Another effort is to carry out a patrol. Polres Ngawi also gives penalty ticket and withhold the wild racing participants’ vehicle. Polres Ngawi made the arrested participants do sports activities as punishment and also contacted their families to pick them up at a time according to the given instructions. The perpetrator of racing needs to more strictly supervise their children.